Trends of business model research: A bibliometric analysis - Julio E. Cuc (Journal of Business Models (JOBM), 2019)
Purpose: The purpose of this article is to provide an overview of the evolution of the business model research while identifying the leading trends and suggesting future research directions. Design/Methodology/Approach: The study consists of bibliometric analysis, and bibliographic data visualization using the Web of Science (WoS) database, and cluster analysis using the VOSViewer software. Findings: The results reveal the exponential growth of the topic favored within the academic literature. The analysis identified eight clusters of co-words in the field of the business model (BM). Five relevant research trends were identified in which the topic of the business model (BM) would develop in the next years. Research limitations: The analysis focuses on the field of management, business, finance, and economics literature. The paper describes the research activity concerning a bibliometric analysis. Therefore it does not take into consideration the quality of the publications and methodological issues. Practical Implications: This study may serve as a model providing useful information for academic and practitioners to analyze the topic of the business model (BM) within a certain discipline, as well as to identify research areas that need more attention to come up with theoretical and practical implications. Originality/Value: The analysis structures and consolidates the concept of the business model (BM) in the academic research, providing valuable insights. It identifies future themes for the development of the field and its consolidation within the academic and business literature.
Keywords: 650; Business model research; bibliometrics; co-word analysis; research trends; bibliographic mapping